A Study of Rashtriya Madhyamik Shiksha Abhiyan (RMSA) on Girls Education with Special Reference to Achievement, Test Anxiety and School Adjustment - Gehlot, Sunita; Choudhary, Divya (JOURNAL OF INDIAN EDUCATION, 2019)
The present study attempted to find out the effectiveness of the RMSA programme in government schools on Class X students in relation to their achievement, test anxiety and school adjustment. The sample comprised 400 students studying in different division of Jodhpur, i.e., Pali, Jalore, Barmer, Jaisalmer and Jodhpur districts. Test Anxiety questionnaire was constructed by A. Kumar, the School Adjustment inventory was prepared by N.M. Bhagia and self-constructed science achievement test were used to collect data. It was found that the achievement of rural girls was higher as compare to urban girls but the test anxiety was lower in urban girls in contrast to rural girls, whereas the school adjustment was excellent in urban girls as compared to rural girls due to the facilities provided by the RMSA Programme. Low, negative and significant relationship was found between achievement and test anxiety of rural and urban girls. Low, positive and significant relationship was found between rural and urban girls in relation to their achievement and school adjustment. Moderate, negative and significant relationship was found between test anxiety and school adjustment. This was a benchmark study that provides concrete information from the perception of students that a quality improvement programme must be offered through the RMSA as it is a very effective programme for quantitative and qualitative improvement of the students.